2011
DOI: 10.1007/s11999-011-1770-9
|View full text |Cite
|
Sign up to set email alerts
|

Defining Racial and Ethnic Disparities in Pain Management

Abstract: Background Substantial pain prevalence is as high as 40% in community populations. There is consistent evidence that racial/ethnic minority individuals are overrepresented among those who experience such pain and whose pain management is inadequate. Questions/purposes The objectives of this paper are to (1) define parameters of and summarize evidence pertinent to racial/ethnic minority disparities in pain management, (2) identify factors contributing to observed disparities, and (3) identify strategies to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(227 citation statements)
references
References 87 publications
(124 reference statements)
7
215
1
1
Order By: Relevance
“…However, these differences were narrow and clinically unimportant. Our results, particularly on preoperative pain, are in agreement with the ones reported by Mossey [16] who performed an extensive literature review focused on racial/ethnic minority disparities in pain management and showed that individuals from racial/ethnic minorities are at increased risk of serious or activity-limiting pain. Regarding preoperative functional status outcomes, the senior author showed in a smaller case-series [13] that black patients undergoing total joint arthroplasty had lower scores than white patients in most outcome measures.…”
Section: Discussionsupporting
confidence: 92%
“…However, these differences were narrow and clinically unimportant. Our results, particularly on preoperative pain, are in agreement with the ones reported by Mossey [16] who performed an extensive literature review focused on racial/ethnic minority disparities in pain management and showed that individuals from racial/ethnic minorities are at increased risk of serious or activity-limiting pain. Regarding preoperative functional status outcomes, the senior author showed in a smaller case-series [13] that black patients undergoing total joint arthroplasty had lower scores than white patients in most outcome measures.…”
Section: Discussionsupporting
confidence: 92%
“…First, our results could help health service providers to refocus their resources. For example, we found that pain, nausea and vomiting were highly undesired outcomes, hence, clinicians and healthcare professionals should dedicate some preoperative time for patient education on pain management (26)(27)(28)(29) and postoperative acute pain management. A previous study (25) had found that overall pain management systems can be improved by education on realistic pain expectations and coping strategies preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…10 Pain is also correlated with existing physical disability and depression. Interestingly, experience of pain is also thought to differ according to an individual's ethnic background, 11 amongst others due to ethnic associations with different underlying conditions, such as for example diabetes mellitus. 12 Studies examining cultural reactions to pain have focused on white American and African American populations, showing a higher sensitivity in the latter group, as well as more extensive resulting physical limitations, reduced activity and increased anxiety.…”
Section: Prevalence and Population Characteristicsmentioning
confidence: 99%